The role of digital technology in providing education, training, continuing professional development and support to the rural health workforce. Issue 2 (18th February 2021) - Ramsden, Robyn; Colbran, Richard; Christopher, Ellice; Edwards, Michael
Abstract : Purpose: Education, training and continuing professional development are amongst the evidence-based initiatives for attracting and retaining rural and remote health professionals. With rapidly increasing access to and use of digital technology worldwide, there are new opportunities to leverage training and support for those who are working in rural and remote areas. In this paper we determine the key elements associated with the utility of digital technologies to provide education, training, professional learning and support for rural health workforce outside the University and tertiary sector. Design/methodology/approach: A scoping review of peer-reviewed literature from Australia, Canada, US and New Zealand was conducted in four bibliographic databases – Medline complete, CINAHL, Academic Search complete and Education Complete. Relevant studies published between January 2010 and September 2020 were identified. The Levac et al . (2010) enhanced methodology of the Arksey and O'Malley (2005) framework was used to analyse the literature. Findings: The literature suggests there is mounting evidence demonstrating the potential for online platforms to address the challenges of rural health professional practice and the tyranny of distance. After analysing 22 publications, seven main themes were found – Knowledge and skills ( n = 13), access ( n = 10), information technology ( n = 7), translation of knowledge into practice ( n = 6), empowerment and confidence ( n = 5), engagement ( n = 5) and the need for support ( n = 5). Ongoing evaluation will be critical to explore new opportunities for digital technology to demonstrate enhanced capability and retention of rural health professionals. Originality/value: To date there has been limited examination of research that addresses the value of digital platforms on continuing professional development, education and support for rural health professionals outside the university and tertiary training sectors.